PENGEMBANGAN STRATEGI BISNIS DENGAN ANALISIS SWOT PADA UD. BAROKAH SUMENEP - Unsul Abrar; Ahmad Ghufrony; Moh. Kurdi (PRODI AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TJUT NYAK DHIEN (UTND), 2022)
Profit organizations or business units should and should have a certain schedule or time for how to control or evaluate how to develop or run their business while guarding against certain failures that can hinder the smooth running of the business process. UD Barokah is a business that has been established and developed for a long time, so it is necessary to develop a UD business strategy. Barokah in increasing the business unit's revenue, this study uses the SWOT Matrix, the analytical tools used in formulating corporate strategy are the IFE matrix, EFE matrix, IE matrix as for internal factors that can influence UD's business development. Barokah is quality, labor availability, workforce in the area where UD Management is carried out by UD management. Barokah is already a process that has been at a level that can be said to be very professional even though most are relatives, the production results are in accordance with the general market UD. Barokah in the village of West Pandan carries out the production and sales process, external factors that can affect UD business development. Barokah is a raw material that is easy to obtain and easy to establish kinship with various parties such as suppliers or distributors and good response from suppliers and distributors, while some threats such as raw material prices which are sometimes uncertain can be a challenge in itself, from various alternatives that can be a strategy future business development of UD. Barokah is to maintain the quality that has been in demand by the market so far